Frequency of Myocardial Bridging in Patients With Coronary Artery Disease Undergoing CT Angiography - Mushtaq, Komal; Pasha, Nazahat; Zafar, Umama (Biological and Clinical Sciences Research Journal, 2025)
Coronary artery disease (CAD) is a major cause of morbidity and mortality in South Asia, including Pakistan. Myocardial bridging (MB), a condition where a coronary artery tunnels through the myocardium, has been linked to myocardial ischemia and arrhythmias. This study aimed to determine the prevalence of MB in patients with atherosclerotic CAD undergoing CT coronary angiography in a tertiary care hospital in Pakistan. Methods: Chaudhry Pervaiz Elahi Institute of Cardiology, Multan, conducted a descriptive cross-sectional study from July to December 2024. A total of 181 patients aged 40–70 years with a clinical diagnosis of atherosclerotic CAD were enrolled. Myocardial bridging was assessed using 64-slice multi-detector CT angiography. Data were analyzed using SPSS version 25, and associations between clinical variables and MB were determined using Chi-square tests. Results: The mean age of participants was 57.3 ± 8.1 years, with a male predominance (56.9%). Hypertension was the most common comorbidity (64.6%). Myocardial bridging was detected in 18 patients (9.9%), with the mid-segment of the left anterior descending (LAD) artery being the most commonly involved (77.8%). No significant associations were found between MB and clinical risk factors (p > 0.05). Conclusion: Myocardial bridging was present in 9.9% of CAD patients, with the mid-LAD segment being most commonly affected. Given the diagnostic accuracy of CT coronary angiography, its use in CAD assessments may aid in detecting this clinically significant anomaly.